Potential Prospects for Population and Infrastructure in 2045 on Supporting Development in Nduga Regency - Charley M. Bisai; Pisi Bethania Titalessy; Marsi Adi Purwadi; Yundy Hafizrianda (AIBPM Publisher, 2024)
Adequate population and infrastructure are required for the growth of the economy. It is crucial for a country to have decent facilities since it is critical to home life as well as economic operations. The increase in population is a proportional enhancement of facilities and infrastructure. Nduga regency is one of the districts in the Papua Pegunungan province. It is an expansion area of Jayawijaya regency in 2008 which has the potential for abundant population and natural resources. However, there is still a lack of research in this district. Therefore, this study aims to determine potential prospects for population and the availability of residential infrastructure in Nduga regency to support development in 2045. The method used is population projection analysis and the projection of facilities and infrastructure of education, health, economy, and road. The expected output is the availability of residential facilities and infrastructure in Nduga regency. In 2045, the population in Nduga regency has the potential to increase to 172,876 people and with such a population. Hence, it is necessary to provide school buildings, health facilities, as well as additional economic facilities and road.